O percurso da disciplina escolar biologia no currículo das escolas públicas do estado do Maranhão (1893-1943) - LEITE, Fabiana de Araujo (2024)
The History of School Disciplines is a field of study that falls within the area of the History of Education and makes it possible to understand the perspective of the construction of disciplines through teaching content, their organization and their purposes, thus making it possible to discuss the school of the past and understand the school of the present. The general aim of this work was to understand how the subject of Biology was implemented in the curriculum of public schools in the state of Maranhão, based on documentary sources from the organization of education in Maranhão between 1893 and 1943. The methodology used in this study was qualitative, documentary, exploratory and historiographical. The documentary analysis used sources that deal with the inclusion of the school subject Biology in education in Maranhão, such as: Public Instruction Regulations, Teaching Programs, Government Reports, Laws and Decrees. When processing the data, criteria were taken into account such as: the social and global context of the document; the author (or authors) of the documents; authenticity and reliability; the nature of the text and, finally, the key concepts and internal logic (Cellard, 2018), which made it possible to draw out meanings related to the school subject Biology and form three categories presented in the form of subsections. The results show that the implementation of the subject studied, in the stipulated period, went through many changes and was presented in different ways in the two schools of reference at the time, the Liceu Maranhense and the normal course at the Escola Normal/Instituto de Educação do Maranhão. It was observed that in the 19th century, the school subject Biology was present in the curriculum of the Liceu Maranhense, in addition to other branches called Zoology, Botany and Geology, which were taught in two formats (sometimes together and sometimes separately). In the same period, the Normal Course included Natural History and Hygiene in its curriculum. At the beginning of the 20th century, Biology was removed from secondary education at the Liceu Maranhense, and the term Natural History appeared, consisting of branches already present in the curriculum, as well as the inclusion of another branch, called Mineralogy. Soon afterwards, the subjects General Biology and Hygiene were included as part of the complementary secondary education course. For the Normal Course of this period, the subject of Natural History was still present. It was only with the creation of the Maranhão Institute of Education, in the context of the Estado Novo, that the subject with the terminology Biology appeared in the first year of this course.